Incidence and Mechanisms of Coronary Perforations during Rotational Atherectomy in Modern Practice - Yen-Hsiang Wang; Wei-Jhong Chen; Yu-Wei Chen; Chih-Hung Lai; Chieh-Shou Su; Wei-Chun Chang; Chi-Yen Wang; Kae-Woei Liang; Tsun-Jui Liu; Wen-Lieng Lee (Journal of Interventional Cardiology)
Objective. Heavy calcifications remain formidable challenges to PCI, even for well-experienced operators. However, rotational atherectomy (RA)-induced coronary perforations (CPs) still could not be obviated. This study was to explore incidence and mechanisms of RA-induced CP in real-world practice. Knowing why CPs occur in RA should help operators avert such mishaps. Method. Patients who received coronary RA from April 2010 to December 2019 with keywords related to perforations were retrieved from database. The procedure details, angiography, and clinical information were reviewed in detail. Results. A total of 479 RAs were performed with 11 perforations in 10 procedures among 9 patients documented. The incidence of RA-induced CP was 2.1%. The RA vessels were distributed in different territories, including first diagonal branch. Most CPs could be treated conservatively, but prolonged profound shock predisposed to poor outcome. CPs caused by rotawire tip occurred in 18.2% of cases, inappropriately sized burrs in 18.2% of cases, and rotawire damage with subsequent transection and perforation in another 18.2% of cases. A total of 5 (45.5%) perforations were caused by unintended and unnoticed bias cutting into noncalcified plaques (4, 36.4%) or through calcified vessel wall (1, 9.1%). The mechanisms for certain CPs were unique and illustrated in diagrams. Conclusion. CPs due to RA occur in certain percentage of patients. The mechanisms for CPs are diverse. Wire damage with subsequent transection could occur due to inappropriately repetitive burr stress on the wire body. A significant portion was due to unintended and unnoticed bias cutting into noncalcified plaque or through calcified vessel wall.